Analisis Kompetensi dan Lingkungan Kerja dalam Meningkatkan Kinerja Pegawai (Studi kasus pada Koperasi Konsumen Praja Sejahtera Jawa Barat) - Dindin Burhanudin; Ivon Dwi Apriyanti (LPPM Universitas Koperasi Indonesia, 2025)
This research aims to analyze the influence of competence and work environment on the performance of cooperative businesses. In the context of current economic development, cooperatives play a crucial role in enhancing community welfare. It is expected that human resource competence and work environment quality can significantly contribute to the performance of cooperative organizations. Through a quantitative approach, data was collected from various cooperatives using questionnaires distributed to cooperative managers and members. The analysis results indicate a positive relationship between competence and work environment with the performance of cooperative businesses. These findings provide recommendations for cooperative managers to enhance member competence and create a conducive work environment to improve overall business performance.